ACTIVIDADES FÍSICAS Y DEPORTIVAS EN EL NIVEL UNIVERSITÁRIO (Fiep Bulletin - online, 2023)
The present investigation arose because numerous studies have shown the benefits of physical activity in the individual in terms of their mental, physical and emotional health. Reason for which the main objective was: Describe the development of physical and sports activity of university students; in order to contribute to the elaboration of capacities according to the national reality that allows to improve the quality of life of the same and promote this type of activities at the university level. The methodology had a quantitative approach, of a non-experimental design of a descriptive type. The studied population involved 60 students of the Law and Business Engineering career, from the National University of Itapúa, year 2015, where the sampling was probabilistic with a 95% confidence level and a 5% margin of error. The techniques and instruments used were surveys through questionnaires with closed and structured multiple-choice questions. The results showed that in the male gender they practice more sports than physical activities, due to social conditions, while in the female gender they practice more physical activities in gyms than sports activities. Concluding that there are significant differences between the reasons for practice, depending on gender. For men, the reasons for practice are linked to competition, personal capacity, adventure and social relationships. For women, the most valued reasons are those related to physical fitness, health and personal image.
Keywords: Activity; Physical-Sports; University